Kuesioner Pengetahuan, Sikap, Dan Perilaku Masyarakat Tentang Interaksi Obat Dan Makanan-Minuman: Studi Validitas Dan Reliabilitas - Sari, Okta Muthia; Azizah, Putri Nur; Azizah, Marshanda Wan; Feteriyani, Rina; Rahmatillah, Mustafa (BORNEO JOURNAL OF PHARMASCIENTECH, 2026)
Drug–food interactions may lead to significant health problems, such as increased drug toxicity or reduced therapeutic effectiveness. However, a validated questionnaire in the Indonesian language that comprehensively measures public knowledge, attitudes, and practices regarding drug–food interactions is still lacking. This study aimed to evaluate the validity and reliability of a questionnaire assessing public knowledge, attitudes, and practices related to drug–food interactions. A cross-sectional study was conducted in Banjarmasin, South Kalimantan. Inclusion criteria included patients aged ≥18 years with a history of medication use in the past three months. The questionnaire was adapted and modified from previous studies. The research instrument consisted of a questionnaire covering the domains of knowledge, attitude and behaviour, using a dichotomous scale (Yes/No and Agree/Disagree). Each correct answer was scored as 1 and each incorrect answer as 0. The total score for each domain was calculated and categorised as high or low based on the median value. Validity testing was performed on 52 respondents using Pearson’s correlation coefficient, while reliability testing was assessed using Cronbach’s alpha with SPSS software. Results: The final questionnaire consisted of 5 items in the knowledge domain, 6 items in the attitude domain, and 7 items in the practice domain. All items were found valid (r > 0.273). Cronbach’s alpha values for knowledge, attitude, and practice were 0.682, 0.743, and 0.635, respectively, indicating acceptable reliability. Conclusion: This questionnaire demonstrates good validity and reliability, making it suitable for assessing the public’s knowledge, attitudes and behaviour regarding drug-food and drug-beverage interactions.